English vowel perception by Polish advanced learners of English - Balas, Anna (Cambridge University Press, 2018)
This article examines English vowel perception by advanced Polish learners of English in a formal classroom setting (i.e., they learnt English as a foreign language in school while living in Poland). The stimuli included 11 English noncewords in bilabial (/bVb/), alveolar (/dVd/) and velar (/gVg/) contexts. The participants, 35 first-year English majors, were examined during the performance of three tasks with English vowels: a categorial discrimination oddity task, an L1 assimilation task (categorization and goodness rating) and a task involving rating the (dis-)similarities between pairs of English vowels. The results showed a variety of assimilation types according to the Perceptual Assimilation Model (PAM) and the expected performance in a discrimination task. The more difficult it was to discriminate between two given vowels, the more similar these vowels were judged to be. Vowel contrasts involving height distinctions were easier to discriminate than vowel contrasts with tongue advancement distinctions. The results also revealed that the place of articulation of neighboring consonants had little effect on the perceptibility of the tested English vowels, unlike in the case of lower-proficiency learners. Unlike previous results for naïve listeners, the present results for advanced learners showed no adherence to the principles of the Natural Referent Vowel framework. Generally, the perception of English vowels by these Polish advanced learners of English conformed with PAM's predictions, but differed from vowel perception by naïve listeners and lower-proficiency learners.
Keywords: vowel perception; foreign language speech perception; Polish; English